2015
DOI: 10.1098/rspb.2015.2068
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of early male-killing in horizontally transmitted parasites

Abstract: Early male-killing (MK) bacteria are vertically transmitted reproductive parasites which kill male offspring that inherit them. Whereas their incidence is well documented, characteristics allowing originally non-MK bacteria to gradually evolve MK ability remain unclear. We show that horizontal transmission is a mechanism enabling vertically transmitted bacteria to evolve fully efficient MK under a wide range of host and parasite characteristics, especially when the efficacy of vertical transmission is high. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…Interactions between bacterial lineages within arthropods have been suggested to alter the virulence and population dynamics of the resident bacteria (Magalon et al, 2010 ; Bernhauerová et al, 2015 ; Wood et al, 2016 ). However, only a limited number of large-scale studies pertaining to bacterial communities in ticks and other tick vectors have been conducted to explore these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between bacterial lineages within arthropods have been suggested to alter the virulence and population dynamics of the resident bacteria (Magalon et al, 2010 ; Bernhauerová et al, 2015 ; Wood et al, 2016 ). However, only a limited number of large-scale studies pertaining to bacterial communities in ticks and other tick vectors have been conducted to explore these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assume q = 1, i.e. that all males infected by male-killing bacteria are killed during embryogenesis; this appears to be a norm (Hurst 1991;Groenenboom & Hogeweg 2002) and has also been shown theoretically to be commonly attained by evolution (Bernhauerova, Berec & Maxin 2015). In Appendix S1 (Supporting information), we provide a detailed derivation of the model (eqn 5).…”
Section: N O N -H E R I T a B L E S T E R I L I T Ymentioning
confidence: 99%
“…In a recent theoretical work, Bernhauerova et al . () found that horizontal transmission allows male‐killing parasites with low penetrance to survive, but that these parasites should evolve towards maximum penetrance and vertical transmission. In another study Yamauchi et al .…”
Section: Discussionmentioning
confidence: 99%
“…All these data suggest that the transmission routes of SRDs are more complex than often assumed. Four recent papers have used mathematical modelling to address the issue of the evolutionary impact of horizontal transmission on the evolution of SRD symbionts (Engelstädter & Hurst, ; Yamauchi et al ., ; Ironside et al ., ; Bern‐hauerova et al., ). Most of these studies have focused on the particular case of male‐killing parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation